Vector mechanics for engineers dynamics - Beer, Ferdinand P. (McGraw-Hill, 2010)
"Vector Mechanics for Engineers: Dynamics" provides conceptually accurate and thorough coverage, and its problem-solving methodology gives students the best opportunity to learn dynamics. This new edition features a significantly refreshed problem set. Key features: chapter openers with real-life examples and outlines previewing objectives; careful, step-by-step presentation of lessons; sample problems with the solution laid out in a single page, allowing students to easily see important key problem types; and, Solving Problems on Your Own boxes that prepare students for the problem sets. Forty percent of the problems updated from the previous edition.